Interaction between monetary policy and bank regulation: Lessons for the ECB - Marek Dąbrowski (Center for Social and Economic Research (CASE), 2016)
The European Central Bank (ECB) recently became engaged in macro-prudential policies and the micro-prudential supervision of the largest Euro area banks. These new tasks should help complete financial integration, and make the Euro area more resilient to financial instability risks. However, the multiplicity of mandates and instruments involves a risk of their inconsistency which could compromise the ECB's core price-stability mandate as well as its independence. The experience of central banks during the recent global financial crisis confirms that such risks are not purely hypothetical.
Keywords: E51; E52; E58; G01; G18; G28; 330; monetary policy; macro-prudential policy; banking regulation; banking supervision; money multiplier; money velocity; financial stability; European Central Bank